MALABSORPTION; ACASE OF MICROCYTIC ANEMIA IN PAKISTAN - Muhammad Usman et al (Baqai Journal of Health Sciences)
Introduction: Iron deficiency anemia (IDA) is the most common micronutrient deficiency that has affected more than 1.5 billion individuals worldwide. IDA in Pakistan is quite prevalent. Usually IDA treatment is undertaken per oral but in certain cases a refractory state of anemia develops. This state is usually not taken seriously by clinicians and is overruled. Current study was done to see a prospect of refractory anemia (IDA) in light of malabsorption; one of the major causes of IDA. Material and Methods: IDA diagnosis was carried out by performing CBC along with serum ferritin and serum iron. A total of 100 patients were selected (IDA patients) and were administered with oral FeSO4 stat along with ascorbic acid. Another sample from each IDA patient was taken 2 hours after the dose administration. Individuals showing no elevation in serum iron levels after FeSO4 administration were labelled as patients suffering from malabsorption. Results: A total sum of 100 IDA patients were selected in the study. Among them 95% (n=95) showed response to oral iron administration, while 5% (n=5) showed no response to oral iron and therefore, were suffering from IDA due to malabsorption. Conclusion: This study revealed that a substantial number of IDA patients suffer from malabsorption. Keeping this figure in mind, clinicians should be cautious and should shift to parenteral iron as soon as a refractory anemia is suspected.